The relationship between elements of balaghah and narration in the story of Moses - Anas, Muzammir; Zubir, Badri Najib; Engku Atek, Engku Suhaimi (Universiti Sultan Azlan Shah (USAS), 2018)
This study intends to unravel the balaghah aspect which supports the narrative structure of the story between Moses with the Pious Man in Surah al-Kahf as an effort to highlight the aesthetic value of the story. The two main elements of discussion are given the focal attention in the analysis, namely the balaghah aspects and the narrative structure to demonstrate the coordination between the two elements. This study applies the analytical method by extracting the aspects of balaghah through the conventional approach practiced and introduced by the Abd Al-Qāhir Al-Jurjānī. This approach explains the existence of the close relationship between the balaghah aspect and the narrative technique. The balaghah aspect is the element being analysed however this study attempts to relate the approach with the narrative structures. In analyzing Quranic texts related to Moses with the Pious Man, this study unravels the narrative structure found in the text by examining the balaghah aspects that support the structures. This analysis does not cover other available narratives which are not related to this particular story. This analysis also focuses on the word choice, the arrangement in the text, the rational of using the word and its implication, and the lesson and example derived from the narrative. Hence, with this approach, the analysis is expected to provide answers especially to the priority given by the Quran to certain utterances in supporting the narrative structure of this story in an effort to highlight the compatibility and harmony between the balaghah aspects and the narrative structure, which lure the readers towards the beauty and uniqueness of the language found in the Quran, while simultaneously contribute new findings from different aspects.